Online Diagnose System for Risk of Kidney Failure - Mohd Noh, Noraziah; Zakaria, Zalmiyah; Kasim, Shahreen (International Journal of Advanced Science Computing and Engineering, 2019)
Renal or kidney failure, only a few citizen alert in this renal failure problem. They have a lot of thing to done, and disregard on their healthy matter, especially on organ healthy that it cannot be see directly on our eyes. On that matter, online Diagnosis Renal Failure system is developed to help society to diagnose their healthy on renal failure view. System is developed online to give an advantage to society to achieve or access the system everywhere. System has two major module, diagnosis module and information module. Diagnosis module is the part where the user can make a diagnose. Information module has two sub modules, information on renal failure and information on dialysis center all around city in peninsular Malaysia. The system development is performed on expert system methodology with prototyping as the model. Production rules technique is used to represent knowledge and for searching process pattern matching technique has been use. The system expectantly can give a benefit to society and performing diagnosis in represent the knowledge of expert in medical field.